Tipe peneluran, pengaruh lama ketiadaan inang dan pakan terhadap keragaan reproduksi parasitoid Anagrus nilaparvatae Pang et Wang (Hymenoptera: Mymaridae) - Abdilah, Nurullah Asep; Atmowidi, Tri; Buchori, Damayanti (Perhimpunan Entomologi Indonesia, 2016)
Anagrus nilaparvatae Pang et Wang (Hymenoptera: Mymaridae) is a major egg parasitoid of brown planthopper, Nilaparvata lugens Stal (Hemiptera: Delphacidae). The purpose of this study was to examine the egg development type, the effect of host deprivation and feeding on the reproductive performance of parasitoid. Determination of the egg development type was done by dissecting females of A. nilaparvatae upon emerging. Adult females aged 0, 1, 2, 3, 4, 5, and 6 hours were killed in the freezer. Abdominal of wasp was dissected by micro pin. Mature egg of wasp were calculated and documented. Treatment of host deprivations were conducted by feeding 10% honey solution and depriving female parasitoids of host for 3, 6, 9, 12, and 18 hours consecutively. After treatments, female parasitoids were given hosts every day until the parasitoids died. Another group of parasitoids were given with water and treated with the same lenght of deprivation period. Results showed that the A. nilaparvatae egg development type is proovigenic. The egg maturation of parasitoid has been initiated since it first emerge with 75% mature eggs of potential fecundity. In the conditions provided 10% honey solution or water as feed, reproductive performance of A. nilaparvatae decreased with increasing duration of host deprivation period, include realized fecundity, parasitization rate, and longevity of female wasp. The decline in the reproductive performance was done by host deprivation for 9 to 18 hours. Longevity of female wasps varied from one to three days, with higher and lower values consecutively for 9 and 18 hours of host deprivation period.